1999
DOI: 10.1021/bi981795d
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of Phospholamban in the Presence of Calcium Pump: A Fluorescence Energy Transfer Study

Abstract: Phospholamban (PLB), a 52-amino acid protein, regulates the Ca-ATPase (calcium pump) in cardiac sarcoplasmic reticulum (SR) through PLB phosphorylation mediated by beta-adrenergic stimulation. The mobility of PLB on SDS-PAGE indicates a homopentamer, and it has been proposed that the pentameric structure of PLB is important for its regulatory function. However, the oligomeric structure of PLB must be determined in its native milieu, a lipid bilayer containing the Ca-ATPase. Here we have used fluorescence energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
114
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 25 publications
(51 reference statements)
14
114
2
Order By: Relevance
“…Therefore, it is possible that PLN pentamer initially recognizes SERCA by forming a transient intermediate complex, and this interaction provides the energy to strip a subunit out of the oligomeric assembly, and the released PLN monomer would then rearrange and form a stable complex with SERCA. This model is consistent with previous in vitro experiments, in which the addition of SERCA to wild-type PLN increases the percentage of PLN monomers observed by fluorescence energy transfer experiments (2).…”
Section: Fig 2 Intermonomer Distance Restraints (A)supporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is possible that PLN pentamer initially recognizes SERCA by forming a transient intermediate complex, and this interaction provides the energy to strip a subunit out of the oligomeric assembly, and the released PLN monomer would then rearrange and form a stable complex with SERCA. This model is consistent with previous in vitro experiments, in which the addition of SERCA to wild-type PLN increases the percentage of PLN monomers observed by fluorescence energy transfer experiments (2).…”
Section: Fig 2 Intermonomer Distance Restraints (A)supporting
confidence: 93%
“…Imbalance in the PLN-SERCA interaction leads to deterioration of heart function and cardiomyopathy (1). In vitro experiments have suggested that SERCA binds PLN by stripping a subunit away from the unphosphorylated 30-kDa pentamer, thereby depolymerizing PLN assembly (2,3), but the nature of this interaction is still not understood. In addition to its role as a calcium pump regulator, there have been early ion conductance studies suggesting that PLN is also an ion channel (4).…”
mentioning
confidence: 99%
“…Mutagenesis, molecular biology, and in vivo studies revealed that the PLN pentamer depolymerizes into active monomers that bind and inhibit SERCA (3). Similar conclusions were reached by in vitro fluorescence studies (4). Recently, Young and coworkers (5) have reported a cocrystal formed by SERCA and PLN pentamer, suggesting that the pentameric species also is able to bind SERCA.…”
mentioning
confidence: 54%
“…It was found that the PLN monomer (C41F) is able to reduce Ca 2þ affinity of SERCA to the same extent as the PLN pentamer, but it was not able to reduce the rate of myocardial relaxation (58). Moreover, PLN phosphorylation enhances the population of the pentamer (6), whereas an increase in SERCA expression shifts the equilibrium toward the monomeric species (59). Importantly, this equilibrium plays a crucial role in muscle pathophysiology.…”
Section: Discussionmentioning
confidence: 99%